2021
DOI: 10.1037/pspi0000266
|View full text |Cite
|
Sign up to set email alerts
|

Merged minds: Generalized shared reality in dyadic relationships.

Abstract: Many everyday conversations, whether between close partners or strangers interacting for the first time, are about the world external to their relationship, such as music, food, or current events. Yet, the focus of most research on interpersonal relationships to date has been on the ways in which partners perceive each other and their relationship. We propose that one critical aspect of interpersonal interactions is developing a sense of dyadic, generalized shared reality—the subjective experience of sharing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
145
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(151 citation statements)
references
References 128 publications
(201 reference statements)
6
145
0
Order By: Relevance
“…For instance, social identification has been linked with positive health outcomes [20] and lower turnover intentions [21]. Additionally, shared experiences and a possibility to discuss them allows employees to create 'shared reality' , which increases interpersonal connectedness and trust [22,23]. Purposeful recruitment which considers person-organization fit as it relates to congruence in values that relate to benevolence can facilitate this process [24].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, social identification has been linked with positive health outcomes [20] and lower turnover intentions [21]. Additionally, shared experiences and a possibility to discuss them allows employees to create 'shared reality' , which increases interpersonal connectedness and trust [22,23]. Purposeful recruitment which considers person-organization fit as it relates to congruence in values that relate to benevolence can facilitate this process [24].…”
Section: Discussionmentioning
confidence: 99%
“…Prior work on shared reality has shown that people are especially likely to create a shared reality with those they trust epistemically (as a source of information about the world—see Echterhoff & Higgins, 2017 for a review) and with whom they feel connected (e.g., in‐group members; Echterhoff et al., 2005; Echterhoff et al., 2008; Sinclair et al., 2005; or close relationship partners, Rossignac‐Milon et al., 2020; Rossignac‐Milon & Higgins, 2018). They are also more likely to create shared reality with a group of people with a common feeling or belief (versus with an individual; Echterhoff et al., 2017; Higgins et al., 2007).…”
Section: The Role Of Shared Reality In Making the Right Decisionmentioning
confidence: 99%
“…In a recent study, participants jointly interpreted ambiguous images with an online chat partner. Participants who experienced a greater shared reality with their online partner felt more certain that they knew what was really going on in the images—in other words, they felt that their interpretation of the images was “right” (Rossignac‐Milon et al., 2020). In another study in this paper, romantic dyads were given the opportunity to select a product together—an image print to take home.…”
Section: The Role Of Shared Reality In Making the Right Decisionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also stems from shared realitythe perceived commonality with others of feelings, beliefs and concerns (inner states) about something Hardin & Higgins, 1996). Research has shown that the experience of shared reality predicts certainty (Rossignac-Milon, Bolger, Zee, Boothby, & Higgins, 2020); for example, conversation partners discussing ambiguous images who create a greater sense of shared reality feel more certain of what is truly going on in the images. We propose that cleansing behaviors rooted in shared practices feel truly clean, because people believe they clean in the right way (Higgins, Nakkawita, Rossignac-Milon, Pinelli, & Jun, 2020).…”
Section: Introductionmentioning
confidence: 99%